2022
DOI: 10.1007/s10530-022-02978-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of invasive alien species in the emergence and spread of zoonoses

Abstract: The role of invasive alien species in the transmission dynamics of zoonotic pathogens is often overlooked, despite the rapid escalation in biological invasions globally. Here we synthesise available information on the influence of invasive alien species on zoonotic pathogen dynamics in invaded ranges, focussing on Europe, and identify key associated knowledge gaps. We identified 272 documented interactions between alien species and zoonotic pathogens within invaded ranges. The majority of these involved invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The introduction of non‐native species threatens and adversely affects biodiversity and ecosystems and can affect human health. Threats from mosquitoes, rats, and mice, with their endo‐ and ectoparasites, are well known, but there is an urgent need to raise awareness of the potential risks posed to human health by the transmission of zoonotic diseases by non‐native species (Chinchio et al., 2020; Crowl et al., 2008; Hulme, 2014; Roy et al., 2023; Zhu et al., 2019).…”
Section: Causes Of Novel Interactions Between Humans and Wild Animalsmentioning
confidence: 99%
“…The introduction of non‐native species threatens and adversely affects biodiversity and ecosystems and can affect human health. Threats from mosquitoes, rats, and mice, with their endo‐ and ectoparasites, are well known, but there is an urgent need to raise awareness of the potential risks posed to human health by the transmission of zoonotic diseases by non‐native species (Chinchio et al., 2020; Crowl et al., 2008; Hulme, 2014; Roy et al., 2023; Zhu et al., 2019).…”
Section: Causes Of Novel Interactions Between Humans and Wild Animalsmentioning
confidence: 99%
“…On the other hand, rather few predators of the devil firefish have been recorded within the Mediterranean Sea. These include the dusky grouper Epinephelus marginatus, the white grouper Epinephelus aeneus, the common octopus Octopus vulgaris and the silver-checked toad fish Lagocephalus sceleratus [37,63,64] with the first three under fishing or preying pressure [65][66][67]. For the time being, the water temperature seems to be the only effective constraint in the ongoing dispersal of P. miles within the basin [38,68,69].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Aves Class, up to 971 introduced bird species have been reported in 230 countries ( 7 ). However, only a few studies confirmed the introduction of diseases by alien bird species, mostly restricted to sporadic cases ( 8 ). The most relevant was the historical exportation of feral pigeons ( Columba livia ) from the Mediterranean countries.…”
Section: Introductionmentioning
confidence: 99%
“…This synanthropic species has been proven to carry more than 110 zoonotic pathogens ( 9 ); some of them in high proportions, such as Campylobacter jejuni and Chlamydia psittaci ( 10 ). Other alien species carrying zoonotic pathogens described in the scientific literature are the house sparrow ( Passer domesticus ), the common starling ( Sturnus vulgaris ), and the song thrush ( Turdus philomelos ) ( 8 ). Therefore, health status variables should be included when conducting foreign species risk assessments to evaluate the introduction of new agents and the changes in the epidemiology of existing ones ( 11 ).…”
Section: Introductionmentioning
confidence: 99%